Diagnosis and phylogenetic analysis of bovine leukemia virus in dairy cattle in northeastern Brazil - Pereira, José Gomes; Silva, Cândida de Assunção; Silva, Lucas Diniz; Lima, Cristian Alex Aquino; do Rosário, Carla Janaina Rebouças Marques; Silva, Ellainy Maria Conceição; Oliveira, Maria do Socorro Costa; Ribeiro, Larissa Sarmento dos Santos; Santos, Hamilton Pereira; Abreu-Silva, Ana Lucia; Melo, Ferdinan Almeida (Frontiers in Veterinary Science, 2023)
The enzootic bovine leukosis (EBL) is a chronic viral disease of wide distribution in cattle herds and may take several years for the first manifestation of clinical signs. Most animals do not present clinical signs, however, the economic losses are underestimated due to this disease. Thus, this work aimed to detect and characterize BLV in dairy cattle in the state of Maranhão, northeastern Brazil. For this, blood samples were collected from 176 animals from 8 municipalities in the southeastern state of Maranhão. Bovine blood samples were subjected to DNA extraction and molecular diagnosis using nested PCR assays for BLV, targeting gp51 gene. Positive samples were then sequenced and then subjected to phylogenetic inferences. BLV DNA was detected in 16 cattle (16/176, 9.09%) in 4 municipalities. Phylogenetic analyzes showed that the sequence obtained clustered in a clade containing BLV sequences classified as genotype 6, with a high degree of support. This work brings data on the occurrence of BLV in the northeast of Brazil, and the occurrence of genotype 6 in this location, contributing to the molecular epidemiology of this agent.